Serum Trace Minerals Profile in Anestrus Buffaloes Treated With Different Estrus Synchronization Protocols - Kaurav, Pratipal Singh; Shukla, Suresh Prasad; Bajaj, Nitin Kumar; Singh, Anil Kumar; Khare, Ankur; Manjhi, Vinay; Thakur, Ravi Kumar (The Indian Journal of Animal Reproduction, 2022)
The present study was conducted to analyse the serum trace minerals (copper, cobalt, iron, zinc, manganese and selenium) concentration in postpartum anestrus buffaloes. A total of 24 postpartum anestrus buffaloes were randomly selected after taking reproductive history and gynaeco-clinical examination 10 days apart. These 24 animals were divided into four groups; Group A (Ovsynch), Group B (Heatsynch) and Group C (CIDR plus Ovsynch) and Control group (no treatment) each containing six animals. Blood sample was collected on day 0, 7, 9 and 10 of treatment and serum was analysed for various trace minerals. The mean serum copper level (µg/ml) increased significantly (p
Keywords: Postpartum; anestrus; buffaloes; trace minerals